Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/dme.13417
|View full text |Cite
|
Sign up to set email alerts
|

Fetal overnutrition and offspring insulin resistance and β‐cell function: the Exploring Perinatal Outcomes among Children (EPOCH) study

Abstract: Aims To examine the associations of intrauterine exposure to maternal diabetes and obesity with offspring insulin resistance, β-cell function and oral disposition index in a longitudinal observational study of ethnically diverse offspring. Methods A total of 445 offspring who were exposed (n=81) or not exposed (n=364) to maternal diabetes in utero completed two fasting blood measurements at mean (sd) ages of 10.5 (1.5) and 16.5 (1.2) years, respectively, and an oral glucose tolerance test at the second visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
2
36
1
Order By: Relevance
“…Vohr et al reported that maternal pre-pregnancy weight status and gestational weight gain predicted offspring fat mass at birth [57] and age 1 year [58], even among women without GDM. This positive relationship between maternal weight and offspring adiposity at birth [59] and beyond [49,[60][61][62][63][64] has been confirmed in numerous settings. Moreover, the consequences of pregravid adiposity are detectable across the continuum of maternal BMI and can influence offspring metabolic risk independent of offspring adiposity [64][65][66][67].…”
Section: Maternal Obesitymentioning
confidence: 69%
See 1 more Smart Citation
“…Vohr et al reported that maternal pre-pregnancy weight status and gestational weight gain predicted offspring fat mass at birth [57] and age 1 year [58], even among women without GDM. This positive relationship between maternal weight and offspring adiposity at birth [59] and beyond [49,[60][61][62][63][64] has been confirmed in numerous settings. Moreover, the consequences of pregravid adiposity are detectable across the continuum of maternal BMI and can influence offspring metabolic risk independent of offspring adiposity [64][65][66][67].…”
Section: Maternal Obesitymentioning
confidence: 69%
“…In the Pima Indian study, acute insulin response to infused glucose was 40% lower in adults whose mothers had diabetes during pregnancy than in those whose mothers developed diabetes after delivery, despite no differences in per cent fat mass [48]. In lower-risk populations, maternal GDM has been associated with precursors of type 2 diabetes in offspring even after accounting for offspring BMI, including higher estimated insulin resistance (HOMA2-IR) among youth in EPOCH [49], and higher fasting glucose among adolescents in the Danish National Birth Cohort [50]. Similarly, in an analysis of 587 mother-offspring dyads in Denmark, Kelstrup et al found that adult offspring exposed to maternal type 1 diabetes or GDM had impaired insulin sensitivity and lower disposition index compared with adult offspring of normoglycaemic women, even after adjustment for BMI [51].…”
Section: Pathways Linking In Utero Overnutrition To Type 2 Diabetesmentioning
confidence: 95%
“…For the offspring, exposure to GDM in utero has been linked to an increased risk of childhood obesity and development of T2DM (Sauder et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…GDM increases the risk of the mother developing subsequent type 2 diabetes mellitus (T2DM) by up to 7-fold compared to euglycaemic pregnancies (Melchior et al 2017). For the offspring, exposure to GDM in utero has been linked to an increased risk of childhood obesity and development of T2DM (Sauder et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…additionally as moderate risk in one other domain (Brandt et al, 2014;Derraik et al, 2015;Hrolfsdottir et al, 2015;Maftei et al, 2015;Sauder et al, 2017;Tam et al, 2018;Winham et al, 2006). The four studies that had the lowest risk of bias were rated in only one domain as moderate and in all other domains as low risk (Gaillard et al, 2014;Gaillard et al, 2016;Hochner et al, 2012;Oostvogels et al, 2014).…”
Section: Study Qualitymentioning
confidence: 99%